Literasi Digital sebagai Mediator Kunci antara Pengembangan Karir, Budaya Kerja, dan Kinerja Pegawai - Heriyadi, Heriyadi; Haninun, Haninun (Jurnal EMT KITA, 2026)
Digital transformation in hospitals requires employees to have the ability to adapt to technology to maintain service quality. This study aims to analyze the role of digital literacy as a mediating variable in the influence of career development and work culture on employee performance at Menggala Regional General Hospital. The research approach uses a quantitative method with an explanatory design. The study sample consisted of 80 respondents determined using the Slovin formula from a population of 415 employees, and data were collected using a Likert-scale questionnaire. Path analysis was used to examine the direct and indirect effects between variables, and the Sobel Test to examine the mediating role of digital literacy.